2018
DOI: 10.1111/joor.12606
|View full text |Cite
|
Sign up to set email alerts
|

Prominence of scientific publications towards peri‐implant complications in implantology: A bibliometric analysis using the H‐classics method

Abstract: Current bibliometric analyses of the evolving trends in research scope category across different time periods using the H-classics method in implantology are considerably limited. The purpose of this study was to identify the classic articles in implantology to analyse bibliometric characteristics and associated factors in implantology for the past four decades. H-Classics in implantology were identified within four time periods between 1977 and 2016, based on the h-index from the Scopus database. For each art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 25 publications
3
61
0
1
Order By: Relevance
“…Regarding the field of study, dental materials, dental implantology, periodontology, and oral and maxillofacial surgery represent areas of significant interest within the DOSM category. The results of this study are supported by previous research that demonstrated a greater interest in surgical rather than prosthodontic topics [29]. The notable portion of the analyzed HCPs addresses issues related to the classification, prevalence, incidence, and risk factors of periodontal and peri-implant diseases and conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the field of study, dental materials, dental implantology, periodontology, and oral and maxillofacial surgery represent areas of significant interest within the DOSM category. The results of this study are supported by previous research that demonstrated a greater interest in surgical rather than prosthodontic topics [29]. The notable portion of the analyzed HCPs addresses issues related to the classification, prevalence, incidence, and risk factors of periodontal and peri-implant diseases and conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Second, Scopus is considered the largest abstract and citation search engine of peerreviewed literature. It is designed to facilitate researchers not only to access the scientific data, but to study literature for the purpose of analyses and it has been used in several published bibliometric studies (Chiang et al 2018). Third, Scopus includes a more expanded spectrum of journals (n=12,850) than WoS (n=8,700), and its citation analysis is faster and includes more articles than the citation analysis of WoS (Walsh et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…cause it is considered as the largest abstract and citation search engine of peer-reviewed literature. It is designed to facilitate researchers not only to access the scientific data, but to study literature for the purpose of analyses and it has been used in several published bibliometric studies [58][59][60]. Total citations were higher in Google Scholar when compared to Scopus.…”
mentioning
confidence: 99%